Factors affecting work motivation of employees in small and medium steel enterprises in Long An province - Bich Thuy, Ninh Thi (Technium Education and Humanities, 2022)
Human resources are a very important and valuable asset of organizations. However, how to retain employees, motivate them to work, and contribute to the company’s business performance is an issue that needs special attention. Based on a survey of 220 employees in Small and medium steel enterprises in Long An province, the research project has discovered the influencing factors and their degree of impact on the employee’s work motivation, contributing to improving the efficiency of the Company’s business activities in the coming time.